The mediation effect of preservice teacher attitude toward inclusion for students with autism in South Korea: a structural equation modelling approach. Issue 1 (2nd January 2020) - Hong, Saahoon; Hoon Ryoo, Ji; Lee, Misuk; Noh, Jina; Shin, Jaehyun
ABSTRACT: Giving preservice teachers experience in working with students with autism is essential for successful teacher preparation. Structural equation modelling was employed to identify the factors affecting preservice teachers' attitudes toward the use of inclusive settings for students with autism. The results indicated that their coursework influenced attitudes toward full inclusion both directly and indirectly, but had no effect on their perceptions of partial inclusion and self-contained classroom settings. Preservice teachers' beliefs toward special education exerted a mediation effect between special education coursework and full inclusion. Similarly, preservice teacher attitudes toward students with autism presented a mediation effect between field experience and inclusion.